The Factors That Influence The Financial Performance of Islamic Banks - Evi Maulida Yanti; Andi Syahrum; Agussalim M; Denni; Rahmah Yulianti; Boihaki; Ali Abdullah Amer Bin Al-Shaibah (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: The distinction between sharia and conventional practices has enabled sharia banks to withstand monetary crises. It is crucial to assess Sharia Commercial Banks' performance using capital adequacy ratios, operating expenses to income, net operating margin, and non-performing financing. These metrics help increase bank income through return on assets and address high financing issues, ensuring operational efficiency and alignment with management expectations.Purpose: This research aims to determine the factors that influence the performance of Sharia Commercial Banks which are proxied by return on assets as the dependent variable, capital adequacy ratio, operating expenses to operating income and net operating margin as the independent variable and non-performing financing as the intervening variable.Design/methodology/approach: This research is quantitative research using secondary data through financial reports. The total population from 2017 to 2023 is 16 banks. The analytical method used in this research is panel data regression with the help of the Eviews application through the Chow, Hausman and Lagrange tests.Finding/result: The research results show that the capital adequacy ratio has no effect on non-performing financing, operating expenses to operating income has no effect on non-performing financing, net operating margin has an effect on non-performing financing, the capital adequacy ratio has no effect on return on assets, operating expenses to operating income has an effect on return on assets and net operating margin has no effect on return on assets. Then the indirect influence is that non-performing financing is unable to mediate the influence of capital adequacy ratio on return on assets, non-performing financing is unable to mediate the influence of operating expenses to operating income on return on assets and non-performing financing is unable to mediate the influence of net operating margin on returns. Conclusion: The capital adequacy ratio, operating expenses to operating income and net operating margin have no influence on non-performing financing, then the capital adequacy ratio, net operating margin and non-performing financing have no influence on returns. on assets, while operating expenses to operating income have an influence on return on assets. An indirect influence can be conveyed that non-performing financing is unable to mediate the capital adequacy ratio, operating expenses to operating income, net operating margin to return on assets. This research can be used as a guide for assessing business performance through the factors that influence it.Originality/value (state of the art): In assessing the relationship between capital adequacy ratio, operating expenses to operating income and net operating margin to non-performing financing mediated by return on assets, this research explores the contributing factors to the prosperity of developing countries, especially Indonesia, which can help investors and policy makers in making decisions. appropriate way to improve company performance. Keywords: capital adequacy ratio, net operating margin, return on assets, non-performing financing, operating expenses on operating income